Stora finska ordböcker i ett historiskt perspektiv - Ruppel, Klaas; Sandström, Caroline (LexicoNordica, 2016)
The first dictionary of the Finnish language of greater importance was Ganander’s dictionary from 1787, which remained as a manuscript, and was only published facsimile between 1937 and 1940 (printed version 1997). The second great Finnish dictionary was compiled and published by Lönnrot between 1866 and 1880. The process of making and publishing dictionaries was important for the nationalistic movement in Finland in the 19th and 20th centuries. A dictionary of Finnish dialects was already started in the 19th century; a large archive of dialects was gathered by professionals, but also by what is known as crowdsourcing. For the contemporary Finnish language, three large descriptive and normative dictionaries can be identified. The first, Nykysuomen sanakirja, was published between 1951 and 1961. It was followed by Suomen kielen perussanakirja in the 1990s and Kielitoimiston sankirja at the beginning of the 21st century; both consisting of some 100 000 entries.